Barbados. Annual report 2009 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Presents the results of IICA in Barbados in 2009 related with the state of agriculture and rural life, the implementation of the national technical cooperation agenda, interagency cooperation, horizontal technical cooperation, new opportunities for technical cooperation, and the organized activities